Usefulness of plasma renin activity in predicting haemodynamic and clinical responses and survival during long term converting enzyme inhibition in severe chronic heart failure. Experience in 100 consecutive patients. Issue 3 (September 1985) - Packer, M; Medina, N; Yushak, M; Lee, W H
Abstract : The relation between plasma renin activity before treatment and the haemodynamic and clinical responses to converting enzyme inhibition was determined in 100 consecutive patients with severe chronic heart failure who were treated with captopril or enalapril. Initial doses of captopril produced significant increases in cardiac index and decreases in left ventricular filling pressure, mean arterial pressure, mean right atrial pressure, heart rate, and systemic vascular resistance that varied linearly with the pretreatment value for plasma renin activity. In contrast, there was no relation between the pretreatment activity and the magnitude of haemodynamic improvement after 1-3 months of treatment with the converting enzyme inhibitors, and, consequently, a similar proportion of patients with a high (greater than 6 ng/ml/h; greater than 4.62 mmol/l/h), intermediate (2-6 ng/ml/h; 1.54-4.62 mmol/l/h), and low (less than 2 ng/ml/h; less than 1.54 mmol/l/h) pretreatment value improved clinically during long term treatment (64%, 60%, and 64% respectively). Long term survival after one, two, and three years was similar in the three groups. Estimating the degree of activation of the renin-angiotensin system by measuring pretreatment plasma renin activity fails to predict the long term haemodynamic or clinical responses to converting enzyme inhibitors in patients with severe chronic heart failure, and thus appears to be of limited value in selecting those patients likely to benefit from treatment with these drugs.